Innovation, competition and incentives for R&D - Martin Wörter; Christian Rammer; Spyros Arvanitis (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper analyses the relationship between past innovation output, competition, and future innovation input in a dynamic econometric setting. We distinguish two dimensions of competition that correspond to the concepts of product substitutability and entry barriers due to fixed costs. Based on firm-level panel data for Germany and Switzerland we obtain consistent results for both countries. Innovation output in t-1 as measured by the sales share of innovative products is positively related to the degree of product obsolescence in t, and negatively to the degree of substitutability in t in both countries. Further, we find that rapid product obsolescence provides positive incentives for higher - primarily product-oriented - R&D investments in t+1, while high substitutability exerts negative incentives for future R&D investment.
Keywords: O3; 330; Innovation; R&D; Competition; Innovationswettbewerb; Produktsubstitution; Wettbewerb; Industrielle Forschung; Ökonomischer Anreiz; Theorie; Deutschland; Schweiz